Effectiveness of a Guidance Program Using Reality Therapy in Enhancing Motivation to Play Volleyball among First-Year Middle School Students - Hussein, Ahmed; Zwain , Jennan; Issa , Samah (Journal of Physical Education, 2025)
This study aimed to develop a guidance program based on reality therapy and construct a scale to measure motivation toward playing volleyball among first-year middle school students at Al-Mustafa Boys’ School. The counseling sessions sought to enhance students’ motivation to engage in volleyball. The research question focused on whether motivation could be increased through the proposed program. To achieve this, the researcher used an experimental design with two equivalent groups experimental and control employing pre- and post-tests. The study population consisted of 250 students across five classes in the 2023–2024 academic year. After administering the motivation scale, a purposive sample of 40 students with the lowest scores was selected: 20 for the experimental group, which received the guidance program, and 20 for the control group, which did not. After confirming group equivalence, the counseling sessions were conducted over six weeks, from March 3 to April 14, 2024, totaling 12 sessions at two per week. Post-testing and statistical analyses revealed that several students initially had low motivation levels, and the guidance program positively influenced motivation toward volleyball. Based on these findings, the researcher recommended adopting the program and scale to enhance motivation in physical education and incorporating guidance as an essential part of the school curriculum.